Code and dataframe for: Going with the floe: Sea-ice movement affects distance and destination during Adélie penguin winter movements ... - Jongsomjit, Dennis; Lescroel, Amelie; Schmidt, Annie; Lisovski, Simeon; Ainley, David; Hines, Ellen; Elrod, Megan; Dugger, Katie; Ballard, Grant (Zenodo, 2023)
Collection of code and dataframes used to calculate ice support vector-based metrics and run ice support models in R for Ecology submission. Dataframes: IceSupportDF_envinddatana.RData - Data frame used to run both distance and support models. Code: Final_Distance_Model_Ecology.R - Code used to run and evaluate distance model Final_Support_Model_Ecology.R - Code used to run and evaluate support model ice_vector_metrics_Ecology.R - Code showing mathematical functions listed in manuscript for vector based ice support metrics were calculated ...